Fundamentals of cancer epidemiology - Nasca, Philip C; Pastides, Harris (Aspen, 2001)
Primarily aimed at students in introductory survey courses on cancer epidemiology, this textbook covers the biology of the cell, the use of biomarkers, and the role of genetic factors in cancer research. Also reviewed are the cancer risk factors that are found in the environment or are related to li.
Keywords: Neoplasms; Epidemiology; nádory; epidemiologie